A systematic review of population-based studies examining outcomes in primary retroperitoneal sarcoma surgery. (June 2019) - Peacock, Oliver; Patel, Shailen; Simpson, Jonathan A.; Walter, Catherine J.; Humes, David J.
Abstract: Retroperitoneal sarcomas (RPS) are rare mesenchymal tumours. Their rarity challenges our ability to understand expected outcomes. The aim of this systematic review was to examine 30-day morbidity and mortality, overall survival rates and prognostic predictors from population-based studies for patients undergoing curative resection for primary RPS. A systematic literature review of EMBASE, MEDLINE, PUBMED and the Cochrane library was performed using PRISMA for population-based studies reporting from nationally registered databases on primary RPS surgical resections in adults. The main outcomes evaluated were 30-day morbidity and mortality and overall survival rates. The use of additional treatment modalities and predictors of overall survival were also examined. Fourteen studies (n = 12 834 patients) reporting from 3 national databases, (Surveillance, Epidemiology and End Results (SEER), the United States National Cancer Database (US NCDB) and the American College of Surgeons' National Surgical Quality Improvement Program (ACS NSQIP)) were analysed. The reported overall 30-day morbidity and mortality were 23% (n = 191/846) and 3% (n = 278/10 181) respectively. Reported use of perioperative radiotherapy was 28%. No study reported loco-regional recurrence rates. Overall reported 5-year survival ranged from 52% to 62%. Independent predictors of overall survival were age of the patient, resection margin, tumour grade and size, histological subtype and receipt of radiotherapy. This review of population-based data demonstrated relatively low 30-day morbidity rates in patients undergoing curative surgical resections for primary RPS. Thirty-day mortality rates were similar to other abdominal tumour groups. There remains a paucity of data reporting recurrence rates, however 5-year survival rates ranged from 52 to 62%. Abstract : This systematic review of population-based studies evaluates the 30-day morbidity and mortality rates in patients undergoing potentially curative surgical resection of primary retroperitoneal sarcoma (RPS). It also examined predictors of overall survival. Morbidity and mortality rates in these patients were 23% and 3% respectively. Five-year survival rates ranged from 52 to 62%. Recurrence rates were not widely reported.